Reduced peripheral activity leading to hepato‐preferential action of basal insulin peglispro compared with insulin glargine in patients with type 1 diabetes1. (10th October 2016) - Mudaliar, S.; Henry, R. R.; Ciaraldi, T. P.; Armstrong, D. A.; Burke, P. M.; Pettus, J. H.; Garhyan, P.; Choi, S. L.; Knadler, M. P.; Lam, E. C. Q.; Prince, M. J.; Bose, N.; et al.
Abstract : Aims: Basal insulin peglispro (BIL), a novel PEGylated basal insulin with a large hydrodynamic size, has a delayed absorption and reduced clearance that prolongs the duration of action. The current study compared the effects of BIL and insulin glargine (GL) on endogenous glucose production (EGP), glucose disposal rate (GDR) and lipolysis in patients with type 1 diabetes. Materials and Methods: This was a randomized, open‐label, four‐period, crossover study. Patients received intravenous infusions of BIL and GL, each at two dose levels selected for partial and maximal suppression of EGP, during an 8 to 10 h euglycemic clamp procedure withd ‐[3‐ 3 H] glucose. Results: Following correction for equivalent human insulin concentrations (EHIC), low‐dose GL infusion resulted in similar EGP at the end of the clamp compared to low‐dose BIL infusion (GL/BIL ratio of 1.03) but a higher GDR (GL/BIL ratio of 2.42), indicating similar hepatic activity but attenuated peripheral activity of BIL. Consistent with this, the EHIC‐corrected GDR/EGP at the end of the clamp was 1.72‐fold greater for GL than BIL following low‐dose administration. At the lower dose of BIL and GL (concentrations in the therapeutic range), BIL produced less suppression of lipolysis compared with GL as indicated by free fatty acid and glycerol levels at the end of the clamp. Conclusions: Compared with GL, BIL restored the hepato‐peripheral insulin action gradient seen in normal physiology via its peripherally restricted action on target tissues related to carbohydrate and lipid metabolism.